PENGARUH EDUKASI ONLINE PERAWATAN KAKI TERHADAP PENGETAHUAN DAN SIKAP PENCEGAHAN ULKUS : Pada Penderita Diabetes Meilitus Di Puskesmas Lawang Gintung Kota Bogor - Desy Sulastri (2020)
Diabetics have 15-40 times the risk of amputation with 15% of them having foot ulcers, so the need for motivation to be able to do foot care independently to avoid bad complications, the aim of this study is to find out the effects of online education about knowledge and prevention of ulcer attitudes in diabetics. This study was a quasi-experimental study with one group pre-post test, the sample used was 31 people treated at the Lawang Gintung Health Center, Bogor City with purpuse sampling techniques with independent variables online foot care education, and the independent variables were knowledge and prevention the attitude of diabetic ulcers. The result of this study indicate there is an influence of foot care online education on knowledge and attitude of ulcer prevention in diabetics.Foot care online education is becoming a new method of primary prevention that can improve knowledge and attitudes to prevent foot ulcers.